Study Protocol for the COVID-19 Pandemic Adjustment Survey (CPAS): A Longitudinal Study of Australian Parents of a Child 0–18 Years - Westrupp, Elizabeth M.; Karantzas, Gery; Macdonald, Jacqui A.; Olive, Lisa; Youssef, George; Greenwood, Christopher J.; Sciberras, Emma; Fuller-Tyszkiewicz, Matthew; Evans, Subhadra; Mikocka-Walus, Antonina; Ling, Mathew; Cummins, Robert; et al. (Frontiers in Psychiatry, 2020)
Background: The COVID-19 pandemic presents significant risks to the mental health and wellbeing of Australian families. Employment and economic uncertainty, chronic stress, anxiety, and social isolation are likely to have negative impacts on parent mental health, couple and family relationships, as well as child health and development. Objective: This study aims to: (1) provide timely information on the mental health impacts of the emerging COVID-19 crisis in a close to representative sample of Australian parents and children (0-18 years); (2) identify adults and families most at risk of poor mental health outcomes; and, (3) identify factors to target through clinical and public health intervention to reduce risk. Specifically, this study will investigate the extent to which the COVID-19 pandemic is associated with increased risk for parents’ mental health, lower wellbeing, loneliness, and alcohol use; parent-parent and parent-child relationships (both verbal and physical); and child and adolescent mental health problems. Methods: The study aims to recruit a close to representative sample of at least 2,000 adults aged 18 years and over living in Australia who are parents of a child 0-4 years (early childhood, N=400); 5-12 years (primary school N=800); and 13-18 years (secondary school, N=800). The design will be a longitudinal cohort study using an online recruitment methodology. Participants will be invited to complete an online baseline self-report survey (20 minutes) followed by a series of shorter online surveys (10 minutes) scheduled every two weeks for the duration of the COVID-19 pandemic (i.e., estimated to be 14 surveys over 6 months). Results: The study will employ post stratification weights to address differences between the final sample and the national population in geographic communities across Australia. Associations will be analyzed using multilevel modeling with time-variant and time-invariant predictors of change in trajectory over the testing period. Conclusions: This study will provide timely information on the mental health impacts of the COVID-19 crisis on parents and children in Australia; identify communities, parents, families, and children most at risk of poor outcomes; and, identify potential factors to address in clinical and public health interventions to reduce risk.